Larvicidal Effect of Secondary Metabolites of Three Fungi against Cx.quinquefasciatus (Diptera:Culicidae) - Abd Alameer, Ali (Al-Qadisiyah Journal of Pure Science, 2021)
The larvicidal effect of secondary metabolites of Verticillum lecanii,Pencillium chrysogenum and Aspergillus niger against filaria vector Cx.quinquefasciatus was investigated. efficacies have been tested at four different concentrations of secondary metabolites of mentioned fungi (25,50,75,100)ppm .larvicidal efficacy demonstrates that larval mortality was related to concentration, exposure time and larval age. Higher mortality was observed at high concentration, moreover mortality increased when exposure time increased , additionally , the older larvae were more resistant to fungal filtrate. Also, it was perceptible that larvae of Cx.quinquefasciatus have a chieved higher mortality for V.lecanii, at the concentration (100ppm )after 24 ,48,and 72 hrs for first instars were....